Analysis of Coastal Community Economic Empowerment Strategy Through Turtle Conservation in Apar Village, North Pariaman District - Damanhuri, Harfiandri; Suparno, Suparno; Munzir, Abdullah; Aisyah, Siti (Universitas Islam Lamongan, 2025)
Indonesia's coastal areas boast high biodiversity, yet their communities still face economic constraints. Turtle conservation has the potential not only as a conservation effort but also as a basis for economic empowerment of coastal communities. This study aims to identify forms of community involvement in turtle conservation that impact economic welfare; and to develop strategies for economic empowerment of coastal communities based on turtle conservation through a participatory and collaborative approach. The study was conducted in Apar Village, Pariaman City, using exploratory descriptive quantitative methods using SWOT analysis. Data were collected through questionnaires, interviews, and documentation. The results indicate active community involvement in conservation activities such as nest monitoring, hatchling releases, tourism education, and souvenir production, which have begun to have positive economic impacts. The SWOT analysis indicates the strategy's position in the Strength–Opportunity (SO) quadrant with a difference score of +1.79 (internal) and +1.58 (external). This indicates that community strengths can be utilized to seize opportunities for conservation-based economic development. Suggested strategies include integrated ecotourism development, entrepreneurship training, strengthening local institutions, and cross-stakeholder collaboration. This study concludes that turtle conservation in Apar Village has dual potential as an instrument for environmental conservation and a driver of the local economy in a sustainable manner.